Metode Pembelajaran Kitab – Kitab di Pondok Pesantren Na/Hdlatul Muslimat (NDM) Surakarta Tahun Pelajaran 2024/2025 - Muhammad Isa Anshory; Warih Nurul Hidayati; Sholekhah Nur Afifah; Nur Ali Rahmatullah (Institut Nalanda, 2024)
This study aims to find out the methods used in learning books and also the supporting and inhibiting factors in the learning process of books at MTs NDM Surakarta Boarding School. This type of research is a qualitative descriptive research, and the data collection tools are in the form of observation, interviews, and documentation. Data analysis is carried out by giving meaning to the data obtained and then drawing conclusions.From the data collection process and data analysis carried out, the results were obtained in the form of learning resources (books) used in learning at the MTs NDM Islamic Boarding School, namely the book nahwu, shorof, tajwid, minhajul muslim, riyadhus sholihin, shofatut tafsir, muthola'ah insa'.The book learning process at the MTs NDM Boarding School involves asatidzah with students in conveying a series of learning objectives with interesting strategies. The values of moral education at the MTs NDM Islamic Boarding School contained in the book Minhajul Muslim are a process of changing behavior, student ethics, towards a better life and direction which is sourced from the Qur'an Hadith. The punishment of students when violating the rules of the Islamic Boarding School is as follows: The lightest punishment (reprimanded, Advised, picketed, memorized / read the Qur'an. Meanwhile, the punishment that is severe is getting an SP (Warning Letter / DO (Drop Out).